On the role of context in business process management. Issue 3 (June 2016) - Brocke, Jan vom; Zelt, Sarah; Schmiedel, Theresa
Highlights: We emphasize the importance of going beyond a one-size-fits-all approach to BPM. We suggest a comprehensive consideration of contextual factors in BPM. We propose a framework to identify BPM contexts along four dimensions. Abstract: Business Process Management (BPM) has proven successful to help organizations improve and innovate, and its application has grown in scope and context. One essential problem related to this development is that the BPM body of knowledge does not account for a broader variety of business contexts. On the contrary, most approaches, methods, or models in BPM suggest one way forward, and we recognize that BPM projects following a one-size-fits-all approach are prone to fail, since they do not sufficiently consider situational requirements. In this viewpoint article, we argue that BPM needs to be contextual in order for projects to be most efficient and effective. We observe a lack of research on how to identify and characterize business contexts relevant for tailoring the right BPM approach. Therefore, we examine contextual factors that influence BPM and propose a framework to identify the context in which BPM is applied. We define context in BPM as situational factors related to goal-, process-, organization-, and environment-dimensions. Our viewpoint article not only creates awareness for contextual BPM, it also intends to stimulate research on the role of context in BPM and to help practitioners better understand the specific business context in which BPM initiatives are applied.